The Effect of Modified Training Equipment on Reaction Time for Goalkeepers at Bajo Soccer School - Muhammad Mahensyah; Imam Pribadi; A. Heri Riswanto (Universitas Negeri Semarang, 2024)
The goalkeeper is a position in soccer where the player is allowed to use their hands to catch or deflect the ball, as long as it is within the penalty area. The goalkeeper’s role is crucial to the team, as they are responsible for preventing the ball from entering the goal, which is the main objective of the game. This research was conducted with the aim of improving the goalkeeper’s reaction time in handling match situations that often require quick and accurate decision-making. The method used in this study is a quantitative experimental approach with a one-group pre-test and post-test design. The research revealed that there was a significant improvement in the goalkeeper’s reaction time after modifying the training equipment used. At the pre-test stage, the goalkeeper recorded an average score of 29.50, while at the post-test stage, the average score increased to 54.33. This increase indicates that the modification of the training equipment has a significant effect on improving the goalkeeper’s reaction. This improvement in reaction ability is very important because it can improve goalkeepers’ performance in real matches, helping them make faster and more precise decisions in decisive situations, so the effectiveness of the training tool modification used in this study can be recognized as one of the important factors in goalkeeper skill development.